The Simple Chordate Ciona intestinalis Has a Reduced Complement of Genes Associated with Fanconi Anemia. (January 2016) - Stanley, Edward C.; Azzinaro, Paul A.; Vierra, David A.; Howlett, Niall G.; Irvine, Steven Q.
Fanconi anemia (FA) is a human genetic disease characterized by congenital defects, bone marrow failure, and increased cancer risk. FA is associated with mutation in one of 24 genes. The protein products of these genes function cooperatively in the FA pathway to orchestrate the repair of DNA interstrand cross-links. Few model organisms exist for the study of FA. Seeking a model organism with a simpler version of the FA pathway, we searched the genome of the simple chordate Ciona intestinalis for homologs of the human FA-associated proteins. BLAST searches, sequence alignments, hydropathy comparisons, maximum likelihood phylogenetic analysis, and structural modeling were used to infer the likelihood of homology between C. intestinalis and human FA proteins. Our analysis indicates that C. intestinalis indeed has a simpler and potentially functional FA pathway. The C. intestinalis genome was searched for candidates for homology to 24 human FA and FA-associated proteins. Support was found for the existence of homologs for 13 of these 24 human genes in C. intestinalis. Members of each of the three commonly recognized FA gene functional groups were found. In group I, we identified homologs of FANCE, FANCL, FANCM, and UBE2T/FANCT. Both members of group II, FANCD2 and FANCI, have homologs in C. intestinalis. In group III, we found evidence for homologs of FANCJ, FANCO, FANCQ/ERCC4, FANCR/RAD51, and FANCS/BRCA1, as well as the FA-associated proteins ERCC1 and FAN1. Evidence was very weak for the existence of homologs in C. intestinalis for any other recognized FA genes. This work supports the notion that C. intestinalis, as a close relative of vertebrates, but having a much reduced complement of FA genes, offers a means of studying the function of certain FA proteins in a simpler pathway than that of vertebrate cells.